Incidencia de anorexia nerviosa en mujeres pospuberales de colegios particulares y fiscales de la zona céntrica de Machala - Astudillo Román, María E. (2009)
The present investigation on the dysfunctions of the feeding in students was carried out in the parish Machala of the City of Machala that had as objectives 1. To investigate the incidence of risks of dysfunctions of the feeding like nervous anorexy, 2. To identify the factors that predispose to suffer nutritious dysfunction as nervous anorexy in presenting nervous anorexy is more frequent for adolescent women of the fiscal or particular schools, 4. To determine which the age is inside the most vulnerable evaluated by maintenance, socioeconomic, IMC, alimentary conditions, gineco-obstetric records, lifestyles so much in the fiscal schools as matters applying the questionnaire SCOFF and the test EAT 26. Having the results of 36% of students of fiscal schools and 45% of particular facilities possesses risks of nervous anorexy.